Direct Medical Costs of Diabetes Mellitus Treatment for Patients with Cardiovascular and Renal Complications - Fadila, Rizki; Purnamasari, Ayu Tyas; Citra Dewiyani, A.A. Istri (UI Scholars Hub, 2025)
Type 2 Diabetes Mellitus (T2DM) represents a growing global health challenge with significant clinical and economic implications, notably in Indonesia. The burden is intensified by renal and cardiovascular complications, especially among National Health Insurance beneficiaries. This retrospective study evaluated the direct medical costs of hospitalized T2DM patients with such complications at a type B hospital from 2019 to 2022. Costs were analyzed from both healthcare provider and payer perspectives, covering medical services, medical support services, pharmaceuticals, and other support services. Of the 192 patients reviewed, most were male (57.8%), aged 45–64 years (72.4%), with hospital stays of 1–5 days (90,1%) and severity level E-4-10-I (100%). Renal complications incur higher treatment costs than cardiovascular complications, with medical support services dominating renal costs and medical services such as doctor and nursing procedures, examinations, and visits contributing most to cardiovascular costs. These results highlight the urgent need for preventive measures, early diagnosis, and innovative treatments to optimize T2DM management and reduce associated economic burdens.